1995
DOI: 10.1164/ajrccm.151.3.7881686
|View full text |Cite
|
Sign up to set email alerts
|

Lower airways inflammation during rhinovirus colds in normal and in asthmatic subjects.

Abstract: Human rhinoviruses (HRV) cause the majority of common colds and are etiologically linked with changes in lower airways physiology and asthma exacerbations. We hypothesized that changes in bronchial mucosal inflammatory cell populations may be responsible for HRV-induced changes in airway reactivity. We examined bronchial mucosal biopsies during experimental infections with HRV serotype 16 and measured changes in histamine reactivity. Seventeen adult volunteers (six atopic asthmatics) had baseline measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
238
1
7

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(252 citation statements)
references
References 0 publications
6
238
1
7
Order By: Relevance
“…No differences in spirometric changes were found between rhinovirus and nonrhinovirus COPD exacerbation, although common colds have been associated with changes in lower airway resistance in normal patients [27]. Changes in lower airway inflammatory indices have been associated with experimental rhinovirus infection [7,28]. It has previously been shown that there are increased inflammatory changes in the lower airway during COPD exacerbation [4].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…No differences in spirometric changes were found between rhinovirus and nonrhinovirus COPD exacerbation, although common colds have been associated with changes in lower airway resistance in normal patients [27]. Changes in lower airway inflammatory indices have been associated with experimental rhinovirus infection [7,28]. It has previously been shown that there are increased inflammatory changes in the lower airway during COPD exacerbation [4].…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, it was found that total symptom score was related to rhinovirus detection but not to IL-6 levels. Experimental rhinovirus infection has also been shown to cause increased inflammatory marker levels in normal subjects and asthmatics, with increases in sputum IL-6 concentration [7,28,29], although COPD patients have not been studied as it is not possible to infect patients with COPD in view of their restricted lung function. Thus IL-6 may play an important part in the pathogenesis of rhinovirus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute viral infection induces lower airway inflammation [56] which may persist long after the infection has resolved [57]. Inflammatory changes including damaged bronchial epithelial, basement membrane thickening and a chronic inflammatory (mainly lymphocytic) infiltrate have been demonstrated in bronchial biopsies from patients with chronic cough [58].…”
Section: Inflammation Cough Reflex Sensitisation and Airway Sensory mentioning
confidence: 99%
“…Serum eosinophil cationic protein (ECP) is known as a marker of activated eosinophils (Venge et al 1999), which release several chemical mediators, reactive oxygen species and proteins such as major basic proteins. Activated eosinophils induce the injury of airway epithelium (Holgate 1997), and RV infection causes activation of eosinophil chemotaxis (Furukawa et al 2004) and eosinophilic infiltration in the bronchial mucosa (Fraenkel et al 1995). These cytokines, adhesion molecules and ECP are known to mediate various inflammatory and immunoregulatory effects (Akira et al 1990;Holgate 1997;Furukawa et al 2004), and may play an important role in the pathogenesis of respiratory viruses infections.…”
mentioning
confidence: 99%